The Principle of the Rule of Law and the Right to Good Governance in the Iranian Legal System - Mohammadali Naserinia; Taha Eslami; Abolfazl Jafari-Sales (Aequitas Magazine)
The principle of the rule of law and the right to good governance in the Iranian legal system are recognized as two fundamental pillars for ensuring citizens’ rights and sustainable development. The rule of law signifies the establishment of justice and the equal enforcement of laws for all individuals in society, which is emphasized in the principles of the Iranian Constitution. In addition, the right to good governance refers to transparency, accountability, and participation in decision-making processes that must be adhered to within public and private institutions. Together, these two principles contribute to the establishment of an efficient and accountable governance system that will foster social and economic development and promote human rights.